2020
DOI: 10.1186/s12870-019-2214-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic and metabolic analysis of wild and domesticated wheat genotypes reveals differences in chemical and physical defense responses against aphids

Abstract: Background: Young wheat plants are continuously exposed to herbivorous insect attack. To reduce insect damage and maintain their growth, plants evolved different defense mechanisms, including the biosynthesis of deterrent compounds named benzoxazinoids, and/or trichome formation that provides physical barriers. It is unclear whether both of these mechanisms are equally critical in providing an efficient defense for wheat seedlings against aphids-an economically costly pest in cereal production.Results: In this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 110 publications
(142 reference statements)
2
37
0
Order By: Relevance
“…However, these experiments were conducted during the seedling stage (2-weeks old) and under controlled growth conditions. Young wheat plants synthesize benzoxazinoids as a defense against insects (Sue, Nakamura & Nomura, 2011;Makowska, Bakera & Rakoczy-Trojanowska, 2015;Batyrshina et al, 2020), but the compounds were not detected in later developmental stages (either juvenile or mature), except for in the dry seeds (Hanhineva et al, 2011). In the metabolic analysis in the present study, we identified three flavonoids, namely 3-caffeoylquinic acid (also known as chlorogenic acid), quercetin-3-O-rutinoside (also known as rutin), and kaempferol-3-glucoside.…”
Section: Discussionmentioning
confidence: 63%
“…However, these experiments were conducted during the seedling stage (2-weeks old) and under controlled growth conditions. Young wheat plants synthesize benzoxazinoids as a defense against insects (Sue, Nakamura & Nomura, 2011;Makowska, Bakera & Rakoczy-Trojanowska, 2015;Batyrshina et al, 2020), but the compounds were not detected in later developmental stages (either juvenile or mature), except for in the dry seeds (Hanhineva et al, 2011). In the metabolic analysis in the present study, we identified three flavonoids, namely 3-caffeoylquinic acid (also known as chlorogenic acid), quercetin-3-O-rutinoside (also known as rutin), and kaempferol-3-glucoside.…”
Section: Discussionmentioning
confidence: 63%
“…Although more resistant cultivars may not assure that the pest populations will be always kept below the economic injury levels, it at least provides a less favorable environment for the aphid pests, with respect to the population growth rate ( Atlıhan et al 2017 ). Emmer is a rich genetic resource for wheat improvement that has been extensively studied ( Nevo 2001 ) but might have weak potential to resist pests, especially during the early growth stage ( Sotherton and van Emden 1982 , Chandrasekhar et al 2018 , Batyrshina et al 2020 ; this study). We therefore advocate that great care be taken to avoid the transmission of genes responsible for suitability to aphids from emmer, as the gene source, to T. aestivum .…”
Section: Discussionmentioning
confidence: 99%
“…Husnot). Subsequent work using the same cultivars as in Chandrasekhar et al (2018) and one bread wheat cultivar revealed increased fecundity of Rhopalosiphum padi (Linnaeus) under both of the tetraploid wheat genotypes than the bread wheat, indicating that the former were more susceptible to aphids ( Batyrshina et al 2020 ). Conversely, Migui and Lamb (2004) observed partial resistance to aphid infestation, as indicated by decreased fecundity of Sitobion avenae Fabricius, in a diploid einkorn compared with tetraploid and hexaploid species of Triticum .…”
mentioning
confidence: 99%
“…Then, 2 cm sections were sampled from the widest part of three leaves: (i) lower leaf (a first leaf from the base), (ii) middle leaf, and (iii) upper leaf. The three leaves were dissected, bleached in 80% (v/v) ethanol, boiled at 90°C for 20 min, and washed with distilled water as previously described ( Batyrshina et al, 2020b ). For trichome visualization, leaves were mounted on microscope slides with the adaxial side facing up, covered with glass coverslips.…”
Section: Methodsmentioning
confidence: 99%
“…Many surface characteristics, including the trichomes, cuticle, epidermis, waxes, and cell walls, can modulate these interactions ( Agrawal et al, 2009 ). The leaf surface of young wheat and barley plants are covered with non-glandular trichomes, specialized epidermal hair-like structures, that might affect aphid movement and reproduction rate ( Leybourne et al, 2019 ; Batyrshina et al, 2020b ; Correa et al, 2020 ). To cope with insect attack, plants adjust their central metabolism by transiently modifying photosynthetic efficiency and remobilizing carbon and nitrogen resources ( Meihls et al, 2012 ; Appel et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%